Muraqabah: Meaningful Adjuvant Therapy for Metabolic Health - Hamid Ashraf; Shehla Sheikh; Mohammad Rashid; Sanjay Kalra (Journal of the Pakistan Medical Association, 2024)
prayerful meditation or religious meditation. This is ameans of connecting to God, while being mindful of hispresence. It also implies seclusion. Muraqabah may be usedas means of improving physical and mental health inpersons with metabolic diseases such as diabetes andhypertension. In this editorial. We share the need to studyand research this potential therapy, we share pragmaticideas as to how muraqabah can be introduced in clinicalpractice, Keywords: Diabetes, hypertension, Islamic meditation,mindful meditation, person centred care, psychosocialaspects.